Gut microbiota dysbiosis aggravates sepsis-induced lung injury by promoting neutrophil extracellular traps and suppressing host integrin defense - Zhao, Zhiyong; Wu, Bingjie (Frontiers in Microbiology, 2026)
BackgroundThe gut-lung axis is central to systemic inflammatory regulation, but the mechanisms by which gut microbiota dysbiosis aggravates sepsis-induced acute lung injury (ALI), particularly through neutrophil extracellular traps (NETs) and integrin signaling, remain unclear. Given the critical need for microbiota-based therapeutic strategies, this study investigates the mechanistic link between gut microbiota, NET formation, and pulmonary endothelial barrier dysfunction.MethodsUsing a cecal ligation and puncture (CLP) sepsis model, control, sepsis, and fecal microbiota transplantation (FMT) groups were compared. Lung injury was assessed via histopathology, wet/dry weight ratios, and bronchoalveolar lavage fluid (BALF) analysis. High-throughput RNA sequencing (GO/KEGG/PPI) identified key targets, validated by lentiviral knockdown/overexpression of ITGAM and ITGB2 in vivo and in vitro [mouse pulmonary microvascular endothelial cells (MPMECs) and neutrophil co-cultures]. NETs were quantified by MPO-DNA ELISA and immunofluorescence.ResultsCLP-induced sepsis triggered severe pulmonary edema, neutrophil infiltration, and NET accumulation, alongside downregulation of ITGAM/ITGB2 and tight junction proteins (β-catenin/ZO-1/VE-cadherin). FMT reduced NETs by 58% (p < 0.001) and restored endothelial barrier integrity. Transcriptomics revealed ITGAM/ITGB2 as central nodes in neutrophil activation and integrin pathways. In vitro, NET exposure increased endothelial permeability (3.1-fold FITC-dextran flux, p < 0.01) and IL-6/TNF-α secretion, while ITGAM/ITGB2 overexpression reversed these effects. Conversely, integrin silencing abolished FMT’s protection, exacerbating ALI.ConclusionWe unveil a novel gut microbiota-NET-integrin axis in sepsis-induced ALI, where microbial dysbiosis promotes NET-mediated suppression of ITGAM/ITGB2, leading to endothelial barrier failure. Our findings position FMT and integrin modulation as promising strategies to mitigate pulmonary vascular dysfunction, advancing the therapeutic potential of microbiota-targeted interventions in critical care.